STUDIES ON COMPARISON OF PROPORTIONAL ON ERROR WITH PROPORTIONAL ON MEASURED VALUE IN PID CONTROLLERS - WAN MOHD RUSHIDI, WAN AMIR HAKIMI (IRC, 2019)
PID Controllers have different algorithms or methods in which the controller action is based on Error or Process Variable (PV). In this paper, it covers about the effect of time delay towards the behaviour of the controller as well as seeing how, the different algorithms of PID, specifically with Proportional Action based on Error and Proportional Action based on PV affects the controller behaviour towards setpoint (SP) changes and Disturbance or Load Changes. Usually, it is addressed as an I–PD controller because only integral action acted on error but for this paper, it will be focusing on ID–P controller when basing the proportional action on PV. The method to test these is using the software MATLAB, specifically Simulink. Based on the findings, Proportional on PV algorithm responds slower than Proportional on Error algorithm. Though, by increasing the value of Kc can improve the response for Proportional on PV algorithm to make it as having similar response with Proportional on Error algorithm that uses the original Kc. As a conclusion, time delay postpones the response of the controller while using the Proportional on PV removes proportional kick in the controller response.